Pengaruh Self Control dan Intensitas Pembelian Item Virtual Terhadap Pengelolaan Keuangan Pribadi Pemain Game Roblox di Karawang - Asyifa Arethania Dayanara Ryu; Ujang Suherman; Thomas Nadeak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
There has been a spike in the purchase of virtual items among gamers due to the fast expansion of the online gaming market, especially on the Roblox platform. When gamers display a lack of self-control and a high intensity of acquiring virtual products, this phenomena may impact their conduct regarding personal money management. Irrational expenditure and a lack of financial stability could emerge from such circumstances. Partially and concurrently, this research intends to examine the impact of self-control and the intensity with which Roblox users in Karawang purchase virtual items on their financial management. An explanatory technique is used by this quantitative investigation. A total of 212 Roblox users in Karawang who had made virtual goods purchases in the past were surveyed using a purposive sample approach. Multiple linear regression was used to analyze the data with the help of SPSS version 26. A player's ability to exercise self-control affects their handling of their money, according to the findings. The intensity of buying virtual items also has a major impact on budgeting. Both factors impact Roblox users' ability to handle their money at the same time. The findings of this research should raise awareness about the significance of self-control while playing video games online and help advance digital financial literacy.